Effects of playing surface on physiological responses and performance variables in a controlled football simulation - Hughes, M. G.; Birdsey, L.; Meyers, R.; Newcombe, D.; Oliver, J. L.; Smith, P. M.; Stembridge, M.; Stone, K.; Kerwin, D. G. (Journal of Sports Sciences, 2013)
In spite of the increased acceptance of artificial turf in football, few studies have investigated if matches are altered by the type of surface used and no research has compared physiological responses to football activity on artificial and natural surfaces. In the present study, participants performed a football match simulation on high-quality artificial and natural surfaces. Neither mean heart rate (171 ± 9 beats/ min vs. 171 ± 9 beats · min-1; P > 0.05) nor blood lactate (4.8 ± 1.6 mM vs. 5.3 ± 1.8 mM; P > 0.05) differed between the artificial and natural surface, respectively. Measures of sprint, jumping and agility performance declined through the match simulation but surface type did not affect the decrease in performance. For example, the fatigue index of repeated sprints did not differ (P > 0.05) between the artificial, (6.9 ± 2.1%) and natural surface (7.4 ± 2.4%). The ability to turn after sprinting was affected by surface type but this difference was dependent on the type of turn. Although there were small differences in the ability to perform certain movements between artificial and natural surfaces, the results suggest that fatigue and physiological responses to football activity do not differ markedly between surface-type using the high-quality pitches of the present study.